Maybe 'I do' : modern marriage and the pursuit of happiness - Andrews, Kevin, 1955- (Ballan, Vic : Connor Court Publishing, 2012)
This book reviews the evidence on the benefits of marriage for society, children, and adults. It argues that healthy, stable, and happy marriages are the optimal institution for promoting individual wellbeing and healthy societies. It reviews the purpose of marriage, changing social values, divorce and one parent families, cohabitation, and the pursuit of personal happiness. Chapters include: The pursuit of marital happiness; Happy, healthy and secure adults; Happy, healthy and well-adjusted children; Happy, healthy and prosperous societies; Changing cultural values; The changing regulation of marriage and divorce; The decline in marital permanence; Soul mates and cohabitation; The growing marriage divide; Policy responses; From culture wars to common good; and Modern marriage and the pursuit of happiness.
Introduction -- Part I. Marriage matters: -- 1. The pursuit of marital happiness -- 2. Happy, healthy and secure adults -- 3. Happy, healthy and well-adjusted children -- 4. Happy, healthy and prosperous societies -- Part II. The new culture: -- 5. Changing cultural values -- 6. The changing regulation of marriage and divorce -- Part III. Maybe 'I do':: the retreat from marriage -- 7. The decline in marital permanence -- 8. Soul mates and cohabitation -- 9. The growing marriage divide -- Part IV. Restoring a marriage and family culture: -- 10. Policy responses -- 11. From culture wars to common good -- 12. Modern marriage and the pursuit of happiness -- Conclusion.
Includes bibliographical references and indexes.
Keywords: Marriage; Home; Families; Australian